Gender Integration in the Art Education Curriculum - Isnawati Mohamad; I Wayan Sudana; Rahina Nugrahani; Abdul Rahman Imran (Sakura Digital Nusantara, 2026)
This study aims to analyze the integration of gender perspectives into the art education curriculum in the Department of Fine Arts and Design, Universitas Negeri Gorontalo. This study is grounded in the importance of strengthening gender awareness in education, particularly in art education, which functions not only as a space for aesthetic development but also as a medium for social reflection and expression. The study employed a qualitative approach, with data collected through curriculum document analysis, analysis of Semester Learning Plans, interviews with lecturers and students, and classroom observation. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings show that the gender integration into the curriculum remains implicit and has not yet been structured systematically. Values of equality, diversity, and humanity are already included, but they have not been clearly operationalized in learning outcomes, teaching materials, learning strategies, or assessment. The study also found a gap between curriculum planning and learning practice, influenced by variations in lecturers’ and students’ understanding of gender issues. Art education has the potential to serve as a pedagogical space for developing gender awareness and critical social reflection, although this potential has not been optimally utilized. The novelty of this study lies in its connection between curriculum document analysis and the lived experiences of educational actors. Therefore, gender integration in art education needs to be directed toward a more explicit, systematic, and responsive curriculum transformation in order to strengthen the role of art education in developing critical and inclusive social awareness.